The Influence Of Principals’ Charismatic Leadership And Teacher Motivation On Teacher Performance At SMP Panca Budi Medan - Ahmad Syarif; Saimara AM Sebayang; Muhamad Toyib Daulay (Universitas Dehasen Bengkulu, 2026)
Teacher performance is a crucial factor in determining the quality of education, as high-performing teachers are able to create effective and innovative learning processes that support students’ competency development. This study aims to analyze the influence of the principal’s charismatic leadership (X₁) and teacher motivation (X₂) on teacher performance (Y) at SMP Panca Budi Medan, as well as to examine the role of motivation as a supporting factor in improving teacher performance. A quantitative approach with an associative explanatory method was employed, involving all 40 teachers of SMP Panca Budi Medan as the research sample. Data were collected through questionnaires, observations, and documentation, and analyzed using validity and reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity), multiple linear regression analysis, and hypothesis testing through partial (t-test) and simultaneous (F-test) analyses. The results indicate that all research instruments are valid and highly reliable, with Cronbach’s Alpha values of 0.977 for X₁, 0.968 for X₂, and 0.962 for Y. The classical assumption tests were fulfilled, indicating that the regression model is appropriate for analysis. Multiple regression analysis reveals that charismatic leadership has a positive and significant effect on teacher performance (B = 0.965; Sig. = 0.000), while teacher motivation also shows a positive effect but is not statistically significant (B = 0.049; Sig. = 0.267). The F-test demonstrates that X₁ and X₂ simultaneously have a significant effect on Y (F = 174.318; Sig. = 0.000), with a coefficient of determination (R²) of 0.904. These findings confirm that charismatic leadership is the primary factor in enhancing teacher performance, while motivation functions as a supporting factor that strengthens the influence of leadership. Principals who demonstrate charismatic leadership while providing motivational support can foster greater teacher professionalism and improve the overall quality of learning.